Evaluation of Tumor Necrosis factor-alpha level in acute leukemic Sudanese patients with pancytopenia - Haj Hamad , Tuga Hassan; M.Ahmed , Enaam Hussein (Technium BioChemMed, 2022)
Objectives: To evaluate intracellular and extracellular TNF-alpha in pancytopenia 'patients with acute leukemia Sudanese patients. Also, to calculate the sensitivity of flow cytometry compared to ELISA technique for extracellular level. Methods: This was a prospective case-control laboratory-based study. The technical work was carried out at the Khartoum Centre of Flowcytometry and University of Khartoum, University of Medical Laboratory Sciences. The sample size was 150; 50 leukemia, 50 leukemia with pancytopenia, and 50 were control groups. Complete blood count (CBC) to confirm selection was evaluated by flow cytometry for CD3, CD4, and CD34, and intracellular TNF-alpha was measured by flow cytometry and extracellular TNF-alpha ELISA. All the participants gave informed consent, approval from Khartoum Flowcytometry Centre, and clearance from the University of Khartoum, Faculty of Medical Laboratory Sciences. Data management and analysis using SPSS. Results: The factor significantly associated with leukemia and leukemia with pancytopenia was age (p-value 0.00) and presence of disease, either AML or ALL (p-value 0.00). The flow cytometer significantly detected intracellular TNF-alpha (p-value 0.012). However, it mainly detected extracellular TNF-alpha in leukemic patients, leukemia patients with pancytopenia, and the healthy control group (p-value 0.01). The sensitivity of flow cytometry (97.5%) is significant (p-value 0.00) for the detection of TNF-alpha in leukemia patients and thus more sensitive than ELISA (79.9%). Conclusion: Flow cytometry is an effective method for detecting TNF-alpha in patients with leukemia and leukemia with pancytopenia. We recommend that flow cytometry be offered in public hospitals and made accessible to patients.